Fair Play Principles in Good Governance: Comparative Regulations and Implementation in Indonesia and Malaysia - Salwa Aulia; Steven Immanuel Simanjutak; Alvian Ajay Chensyah Padang; Wulandari; Mukhlis Mubin (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2026)
The principle of fair play constitutes a fundamental element in modern governance, emphasizing integrity, transparency, and equal treatment in public administration. In Indonesia, this principle is incorporated into the General Principles of Good Governance (AUPB), while Malaysia situates it within administrative instruments including Public Service Ethics and public sector integrity standards. This study analyzes the relevance of fair play principles in realizing good governance through a comparative approach between Indonesia and Malaysia, examining normative foundations, regulatory developments, and implementation practices. The research employs a normative legal approach with comparative methodology, analyzing laws, administrative guidelines, court decisions, and scholarly literature. Findings reveal that although both countries demonstrate commitment to fair play principles, Indonesia confronts challenges in consistent AUPB application and enforcement, while Malaysia encounters issues regarding transparency and effectiveness of public complaint mechanisms. The study confirms that strengthening fair play principles plays a strategic role in enhancing bureaucratic integrity and reinforcing public service legitimacy. Recommendations emphasize regulatory harmonization, improvement of official accountability, and implementation of integrity-based oversight mechanisms. The comparative analysis demonstrates that effective implementation requires not merely normative frameworks but also transformation of administrative culture, capacity building, and sustained institutional support in both countries.